TINJAUAN YURIDIS TERHADAP TINDAK PERDAGANGAN ORANG (TINJAUAN KASUS NO.741/PID.SUS/2016/PN.MDN) - Theresia Simatupang (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
Human trafficking, especially women, is increasingly prevalent, and it makes people more vigilant in supervising children and their environment in order to overcome the development of trafficking in Indonesia, especially in Kota Medan. The main factor in this crime is an economic factor as a big reason for someone to commit such human trafficking. Therefore, parents, the environmental community, and the government have a very important role in overcoming the process and eradicating criminal acts of trafficking in Kota Medan. The process of human trafficking can be prevented by getting closer to the creator and doing positive things in the community. There is the existence of law Number 21 of 2007 concerning Eradication of Human Trafficking as a means of protection from the government for acts of trade of people. In this Law, all matters relating to both human trafficking and the rules and sanctions are regulated.Keyword: Human trafficking, Protection, Overcome